Authority and Epistemology in Islamic Medical Ethics of Women’s Reproductive Health - Ayubi, Zahra (Journal of religious ethics, 2021)
There is a serious lacuna in Islamic medical ethics in considering the category of gender, especially in the consciousness that gender, maleness, femaleness, or non-binary status, affects how patients receive medical counsel and medical care, and interact with religious authorities and care providers. This lack of attention to gender is also true for specifically so-called “women’s health” topics such as assisted reproductive technologies or abortion. This essay argues that in order to be a more ethical discourse, Islamic medical ethics of reproductive health needs to break free from the gendered limitations of male-only authority of jurists and the limited legal frameworks offered by the fiqh genre. Instead it ought to incorporate multiple epistemologies of Islamic ethics.